A hybrid algorithm to combine redundancy and concurrency in virtual network resource pooling. Issue 2 (28th December 2017) - Klapez, Martin; Grazia, Carlo Augusto; Casoni, Maurizio
Abstract: Emergency scenarios pose significant hurdles to wireless communications, especially when these are performed through terrestrial cellular networks. This is because network infrastructures can be damaged, or the sudden surge of network demand can cause unbearable network congestion. Unfortunately, public safety operators employ terrestrial cellular networks to perform data communications and are therefore at risk of being unable to effectively operate in critical situations. Virtual network resource pooling is a software‐defined networking (SDN)‐based network framework that allows collaborative hosts to pool together their network channels to provide connectivity despite the sudden unavailability of network paths or to compensate for high degrees of packet losses. Once hosts' resources are pooled, a dispatching algorithm on the SDN controller is required to enforce a proper policy of packets distribution. This paper presents a dispatching algorithm that is designed to provide fast and reliable transmissions despite lossy and unreliable channels. It works by introducing the minimum amount of packet redundancy that is needed to obtain a packet delivery probability given as a parameter and by using the remaining network resources to augment transfer goodput. Emulation results confirm that with respect to policies that selectively aim to improve goodput or to introduce packet redundancy, this hybrid algorithm can compensate for high packet loss ratios and improve goodput at the same time.